Synthetic osmotic dilators in the induction of labour—An international multicentre observational study. (October 2018) - Gupta, Janesh; Chodankar, Rohan; Baev, Oleg; Bahlmann, Franz; Brega, Eugen; Gala, Anisha; Hellmeyer, Lars; Hruban, Lukas; Maier, Josefine; Mehta, Priyanka; Murthy, Amitasrigowri; Ritter, Melanie; et al.
Abstract: Introduction: To evaluate the effects of synthetic osmotic dilators (Dilapan-S/ Dilasoft) in women who required induction of labour in a large prospective multicentre international observational study. Materials and methods: Primary outcomes were duration of Dilapan-S/Dilasoft insertion (hours), total induction - delivery interval (hours) and the rate of vaginal deliveries within 24 h (%). Secondary outcomes were the number of dilators inserted, Bishop score increase after extraction of Dilapan-S/Dilasoft, complications during induction (uterine contractions, uterine tachysystole and hyperstimulation, effect on the fetus) and post induction (infections and neonatal outcomes), agents / procedures used for subsequent induction of labour, immediate rate of spontaneous labours following cervical ripening period, rate of spontaneous vaginal deliveries, rate of instrumental vaginal deliveries and caesarean sections. RESULTS: Total of 543 women were recruited across 11 study sites, of which, 444 women were eligible for analysis. With Dilapan-S/Dilasoft use of <12 h (n = 188) the overall vaginal delivery rate was 76.6% with 45.7% of these births occurring within 24 h, 66% within 36 h and 75.5% within 48 h from insertion of Dilapan-S/Dilasoft. The mean insertion-delivery interval for this group was 24.3(±10.4) hours. With Dilapan-S/Dilasoft use of >12 h (n = 256), the overall vaginal delivery rate was 64.8%, with 16% of these births occurring within 24 h, 48.4% within 36 h and 54.7% within 48 h from insertion of Dilapan-S/Dilasoft. The mean insertion-delivery interval for this group was 39.1(±29.2) hours. The mean gain in the Bishops score was +3.6(±2.3). The mean number of Dilapan-S/Dilasoft dilators used was 3.8 (±1.1). The overall rate of caesarean section was 30.1%. The overall complication rate was low including infection risk. No adverse neonatal outcome was attributable to the use of Dilapan-S/Dilasoft. Conclusion: Dilapan-S/Dilasoft are safe and effective methods for cervical ripening. Their use is associated with low maternal and neonatal complication rates. Future research should aim at level I clinical trials comparing Dilapan-S to other mechanical or pharmacological cervical ripening agents. Clinical trial registration: https://clinicaltrials.gov/ct2/show/NCT02318173 .